PTS and AICF Combined PAPR Reduction Techniques in Multi-Antenna OFDM Systems - Arifin Arifin; Silvi Fitriah Ditasari; Yoedy Moegiharto; Ida Anisah; Hendy Briantoro (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2019)
A high PAPR value is one of important weaknesses in OFDM systems. Several reduction techniques are applied to reduce PAPR including partial transmit sequence (PTS) as well as clipping and filtering (CF). Adaptive iterative clipping and filtering is a development of iterative clipping and filtering techniques. In this paper, a combination of Partial transmits sequence and adaptive iterative clipping filtering (PTS-AICF) techniques on multi-antenna OFDM transmitters was carried out. The simulation results showed that combined technique application had a better performance than non-combined technique (PTS), either for two or four antennas, and also for different sub block numbers. Performance was also influenced by iterations number on AICF section, the more iterations were used, the better the reduction technique performance was because it produced smaller PAPR 0 value.